Phase separation and selective guest–host binding in multi-component supramolecular self-assembly on Au(111). Issue 75 (5th September 2018) - Yan, Linghao; Kuang, Guowen; Lin, Nian
Abstract : We find a phase separation and selective guest–host inclusion in the self-assembly of trimesic acid, benzenetribenzoic acid and coronene on Au(111). Abstract : Bi-component supramolecular self-assembly of trimesic acid and benzenetribenzoic acid on Au(111) results in phase-separated mono-component porous structures. The pores of the two structures exhibit high selectivity in the binding of coronene molecules.